2022
DOI: 10.3389/fpsyg.2022.953068
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ acculturation in culturally diverse schools - How is the perceived diversity climate linked to intercultural self-efficacy?

Abstract: While in the school context, acculturation is often studied in relation to students of immigrant descent, the current study applies an acculturation framework to teachers mostly representing the mainstream culture. Specifically, we investigated whether teachers’ acculturation attitudes towards their students mediate effects of the perceived cultural diversity climate at school on teachers’ intercultural self-efficacy in culturally diverse classrooms. Analyses were based on reports of 186 teachers (14% of immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…Schwarzenthal et al (2023) found that teachers' perceptions of a multicultural school climate (e.g., offering multicultural events) were positively associated with teachers' CRT self-efficacy at the school level. Similarly, Ulbricht et al (2022) found that German teachers' perceptions of equality and inclusion and cultural pluralism climate were positively associated with their CRT self-efficacy.…”
Section: Teachers' Crt Self-efficacymentioning
confidence: 89%
See 1 more Smart Citation
“…Schwarzenthal et al (2023) found that teachers' perceptions of a multicultural school climate (e.g., offering multicultural events) were positively associated with teachers' CRT self-efficacy at the school level. Similarly, Ulbricht et al (2022) found that German teachers' perceptions of equality and inclusion and cultural pluralism climate were positively associated with their CRT self-efficacy.…”
Section: Teachers' Crt Self-efficacymentioning
confidence: 89%
“…Specifically, CRT self-efficacy refers to the extent to which teachers feel capable of, for example, preparing culturally relevant lessons, reducing cultural conflicts, or creating a supportive classroom climate (Siwatu, 2007; Siwatu et al, 2017). While there is evidence on CRT self-efficacy and teachers’ outcomes (e.g., Comstock et al, 2023; Ulbricht et al, 2022), limited quantitative research has focused on the association between teachers’ CRT self-efficacy and students’ academic and psychological adjustment so far.…”
Section: Teachers’ Crt Self-efficacymentioning
confidence: 99%
“…Consequently, they may find it challenging to work with diverse populations (Geerlings et al, 2018) and experience higher levels of burnout (Gutentag et al, 2018). Recent studies have shown that the multicultural climate within a school may contribute to teachers' sense of efficacy in working with diverse student profiles (Ulbricht et al, 2022;Schwarzenthal et al, 2023). For example, teachers were found to feel more confident in handling the challenges of a multicultural classroom and responding effectively to students with different abilities and cultural backgrounds when they perceived a strong emphasis on inclusion and cultural pluralism in their school context.…”
Section: Teacher Self-efficacy and Responses To Ethnic Victimizationmentioning
confidence: 99%
“…For example, teachers were found to feel more confident in handling the challenges of a multicultural classroom and responding effectively to students with different abilities and cultural backgrounds when they perceived a strong emphasis on inclusion and cultural pluralism in their school context. Additionally, they demonstrated a greater sense of efficacy in promoting positive intercultural relations when their school environment appreciated cultural diversity and adhered to a multicultural curriculum (Ulbricht et al, 2022).…”
Section: Teacher Self-efficacy and Responses To Ethnic Victimizationmentioning
confidence: 99%
“…The school carries out inclusive practice activities, including the planning and deployment of school leaders on the implementation of inclusive education in the whole school, and the activities to promote the development of teachers' professional ability of inclusive education, such as training related to inclusive education, experience sharing and exchange meetings, etc. A good school climate can improve teachers' self-efficacy (Malinen and Savolainen, 2016;Ulbricht et al, 2022), create a more inclusively school climate, and improve teachers' inclusive education efficiency (O'Toole and Burke, 2013;Hosford and O'Sullivan, 2016;Neville et al, 2020). Improving teachers' attitude toward inclusive education (Fu et al, 2021) is an important variable affecting teachers' inclusive education competency, therefore, Hypothesis 1 was put forward: the school inclusive education climate has a positive predictive effect on the inclusive education competency of physical education teachers.…”
Section: Introductionmentioning
confidence: 99%